Kesenjangan Digital dan Dampaknya terhadap Pendidikan - Cendy Lestari; Rahma Dini Pratiwi; Dimas Julian Pratama; Sani Safitri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The digital divide has become an increasingly relevant issue in the last five years, with significant impacts on the global education system. Differences in access to information and communication technology (ICT) in different regions, especially between urban and rural areas, affect the quality and equity of education. This research explores the impact of the digital divide on educational access, including limitations in the use of digital-based learning tools, students' low digital skills and lack of adequate infrastructure. This gap not only hinders teaching and learning but also exacerbates socio-economic inequality. This research also discusses mitigation efforts that have been made by governments, educational institutions and international organizations, as well as recommendations to reduce the gap in the future. Thus, the digital divide needs to be the focus of attention in education reform to create a more inclusive and sustainable education system.